Measuring Income Inequality in Euroland - Miriam Beblo; Thomas Knaus (Luxembourg Income Study (LIS), 2000)
In this paper we propose an aggregate measure of income inequality for all founding countries of the European monetary union. Applying the methodology of the Theil index we are able to derive a measure for Euroland as a whole by exploiting information of two data sets, the European Community Household Panel and the Luxembourg Income Study. The property of additive decomposability further allows us to determine each country's contribution and that of each demographic group to overall income inequality.
Keywords: 330; Einkommensverteilung; Disparitätsmaß; EU-Staaten